PILIHAN RASIONAL PEMILIK LAHAN PEKARANGAN DALAM BERMITRA DENGAN PT ANUGRAH ALAM SUBUR INDONESIA (Studi Kasus di Desa Maron Kecamatan Kademangan Kabupaten Blitar) - sosiologi, WIDODO NURADI (Jurnal Mahasiswa Sosiologi, 2014)
ABSTRACT This study discusses the rational choice land owners to partner with PT Anugrah Alam Subur Indonesia Jabon tree planting program. Management system that developed in Jabon planting program partnership is pattern. This pattern provides the opportunity for local people to enjoy the natural resources owned. This pattern also provides the opportunity for other people who do not have land that could be supporting resources in the process of planting, fertilizing, maintenance and harvesting activities.   The analysis in this study uses the theory of Rational Choice of James Coleman, and the concept of partnership and community empowerment by Jim Ife. This analysis focused on  farmers rational choice and landowners to partner with PT Anugrah Alam Subur Indonesia. This research method is qualitative research deskripsif case study approach and process of data collection is done by observation, interview and documentation.   Key words: Rational Choice and partnerships